2018
DOI: 10.2478/sg-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of genetic diversity in Eucalyptus urophylla S. T. Blake populations with restriction of the number of trees per family

Abstract: Our aim was to verify the effect on gain and genetic diversity through the restriction of the number of trees per family in selection, in order to compose an elite population of Eucalyptus urophylla in two trials under distinct management levels.We studied 166 open-pollinated families of E. urophylla in Anhembi, Sao Paulo State, Brazil under commercial practices, and the same families in Selvíria, Mato Grosso do Sul State, Brazil under lower management level (mainly no mineral fertilization). Mortality, height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…urophylla (Silva et al 2018) showed higher expected heterozygosity. This occurs because the genetic diversity is associated with the environmental variability.…”
Section: Discussionmentioning
confidence: 92%
“…urophylla (Silva et al 2018) showed higher expected heterozygosity. This occurs because the genetic diversity is associated with the environmental variability.…”
Section: Discussionmentioning
confidence: 92%
“…Restriction in number of trees per family enables retention of alleles and high effective population size to sustain diversity in seed crop (Silva et al, 2018). When effective population size is low, relatedness increases giving little option for selection between families.…”
Section: Management Of Seed Orchardsmentioning
confidence: 99%
“…Johnson et al (2001) suggested that 200 outstanding selections would be enough to maintain gain in breeding programs, but to conserve diversity higher number of parent trees (400-1000) is desirable, as observed in SPA 1&2. Diversity in terms of number of families represented would be a prerequisite for advanced generation breeding; and restriction in selection from each family is often practiced to ensure that alleles are conserved in each generation (Silva et al, 2018). Constant seed collection is also a similar strategy as evidenced by only 1 % reduction in number of alleles in CSO 2 compared to CSO 1 (despite big difference in fecundity) whereas there was 9 % difference in alleles per locus between SPA 2 and SPA 3.…”
Section: Management Of Seed Orchardsmentioning
confidence: 99%
See 2 more Smart Citations